Seizing the opportunity to improve patient care: pelvic floor services in 2021 and beyond. (2nd September 2021) - Pakzad, Mahreen; Telford, Karen; Ward, Karen; Keighley, Michael
Abstract : Patients requiring pelvic floor and functional urological, gynaecological and coloproctological surgery were viewed as a low priority even before COVID-19. A consensus report outlines recommendations to improve care and encourage clinicians to help bring about positive changes for patients with pelvic floor problems